PERSONAL PATTERNS OF DEVELOPMENT IN TEACHING CAREER AMONGST PRIMARY SCHOOL TEACHERS IN ISRAEL: CAREER MOTIVATORS, CAREER DRIVEN AND CAREER OPPORTUNITIES - Cochava FARJUN (Studia Universitatis Moldaviae: Stiinte ale Educatiei, 2015)
The research purpose is to expose patterns of personal development in teaching career amongst teachers in elementary schools. The study was conducted with a qualitative methodology, and the data was collected by means of in-depth interviews with the aim of a deep understanding of factors that have affected the research objects. The interviews were focused on several predetermined issues; however, an opportunity was given to the interviewees to tell their story freely, with their words and in their own way and to put forward unpredictable things. In their interviews, the teachers who have developed in their professional career were asked to detail their professional life story. The stories were analyzed by a filed rounded theory approach, which is directed at creating a new theory from data collected in the field. The research findings present three personal development patterns of teachers: career motivated pattern, career driven pattern and career opportunities pattern. Recommendations were suggested regarding teachers' empowerment on the part of their superiors to raise the level of motivation for self-development. MODELE PERSONALE ÎN DEZVOLTAREA CARIEREI DIDACTICE LA PROFESORII DIN ISRAEL: MOTIVAŢIA CARIEREI, MERSUL CARIEREI ŞI OPORTUNITĂŢI DE CARIERĂ Scopul cercetării este de a expune modele de dezvoltare personală în cariera didactică în rândul cadrelor didactice din şcolile primare. Studiul a fost realizat prin utilizarea unei metodologii calitative, iar datele au fost colectate prin intermediul interviului. Datele obţinute au fost analizate în baza unor teorii ce prevăd trei modele de dezvoltare perso- nală a cadrelor didactice: carieră model motivat, model de carieră condus şi oportunităţi de carieră pattern. Recomandă- rile adresate managerilor se referă la necesitatea sporirii nivelului de motivaţie pentru autodezvoltare.